ANALISIS KETERWAKILAN PEREMPUAN DI DPRD KOTA BONTANG PERIODE 2019-2024 - Jusrianty, Jusrianty; Kusuma, Aji Ratna; Daryono, Daryono (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
The affirmative action policy is a part of initiatives to promote women's participation in politics. Hopefully women will understand and support women's issues as a part of gender mainstreaming in Indonesia. This article aims to describe and analyze Bontang City's legislative council's representation of women from 2019 to 2024 period. The data collected from key informants and other informants, also supported by the primary and secondary data. The informants were the officials of political parties, women's leaders and the electorate. The key informants were legislatives council members who have been elected and who have not been elected. The data analysis technique refers to the stages of the Miles & Huberman interactive analysis model, which was conducted by collecting data, reducing data, presenting data, and writing research conclusions. The result shows that women's representation is not optimal, both in terms of the quantity and the substance. This is caused by inhibiting factors which are classified into internal and external factors. Internal factors include the motivation, the socio-economic capability, the social capital capability and the woman’s experience. While external factors include the electoral system, the culture and the public trust, political costs, also the recruitment and candidacy of political parties.